Africa's Pulse, April 2014 : An Analysis of Issues Shaping Africa's Economic Future - World Bank (Washington, DC, 2014)
This Africa's pulse newsletter includes the following The economic outlook for Sub-Saharan Africa remains robust, but growth is vulnerable to lower commodity prices and a slowdown in capital flows, the frequency and strength of growth spurts have increased, and growth has shifted the structure of African economies in favor of the resources and services sectors.